The Effect of New Therapy Zinc on Perinatal Mortality, Prematurity and Placental Ablation - Sardjana Atmadja (ADI Journal on Recent Innovation, 2022)
Zinc is essential for life and is a part of zinc finger proteins, which perhaps represent the largest class of DNA-binding proteins. Zinc finger protein controlled gene expression may be a fundamental aspect of development as well as other processes. Nearly 30 elements are accepted as being essential for some or all organisms. Knowledge of the amounts of zinc in food is necessary for the understanding of the very complex system of zinc metabolism. Zinc content in leucocytes, mononuclear cells, red cells and platelets could be used as a measure of possible zinc deficiency. Almost 300 different enzymes, which include the synthesis and/or degradation of all major metabolites, have zinc as an integral component. AE has been interpreted as being a zinc-deficiency disease. The signs and symptoms of AE are reserved by zinc therapy. The recommended daily intake of zinc in pregnancy and lactation is 15 mg in Sweden and the Scandinavian countries. A woman on continuous zinc therapy for AE had two normal pregnancies. Other contributors to this volume will review these data.